2020
DOI: 10.3389/fimmu.2020.00960
|View full text |Cite
|
Sign up to set email alerts
|

MICAgen Mice Recapitulate the Highly Restricted but Activation-Inducible Expression of the Paradigmatic Human NKG2D Ligand MICA

Abstract: of MICA-specific antibodies. Such immunotolerance for the xenoantigen MICA ideally suits MICAgen mice for anti-MICA-based immunotherapies. Altogether, MICAgen mice represent a valuable model to study regulation, function, disease relevance, and therapeutic targeting of MICA in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…25,32,33,36 MICA transgenic mice bypass this limitation and will be invaluable to assess the safety profile of NKG2D-based therapies. 58 Alternatively, non-human primates can also be utilised in such studies. Of note, chimeric NKG2D receptor T cells were well tolerated by patients with haematological malignancies in a clinical trial reported recently, thus serving as the first evidence of the safety of an NKG2D-based immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…25,32,33,36 MICA transgenic mice bypass this limitation and will be invaluable to assess the safety profile of NKG2D-based therapies. 58 Alternatively, non-human primates can also be utilised in such studies. Of note, chimeric NKG2D receptor T cells were well tolerated by patients with haematological malignancies in a clinical trial reported recently, thus serving as the first evidence of the safety of an NKG2D-based immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the antibodies that inhibit MICA/B shedding or neutralise soluble MICA/B were administered to mice engrafted with MICA/B + tumors but since mice do not have the MICA/B genes they do not serve to toxicological studies 25,32,33,36 . MICA transgenic mice bypass this limitation and will be invaluable to assess the safety profile of NKG2D‐based therapies 58 . Alternatively, non‐human primates can also be utilised in such studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other receptors, such as NKG2D, play decisive roles in tumor immune response. NKG2D is a potent activating immunoreceptor expressed on nearly all cytotoxic lymphocytesthat promotes cytotoxicity against cells expressing NKG2Dligands (MICA/B and ULBP1-6), which are induced bycellular stress, viral infection, or malignant transformation [ 5 ]. Experimental mice models have shown that NKG2D/ligand interactions on NK cells can induce a strong secretion of IL-2 and IFN-γ,which contribute to suppressing tumor growth by modulating tumor microenvironment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%